Contraceptive self-injection through routine service delivery: Experiences of Ugandan women in the public health system - Cover, Jane; Namagembe, Allen; Morozoff, Chloe; Tumusiime, Justine; Nsangi, Damalie; Drake, Jen Kidwell (Frontiers in Global Women's Health, 2022)
Contraceptive self-injection (SI) is a new self-care practice with potential to transform women's family planning access by putting a popular method, injectable contraception, directly into the hands of users. Research shows that SI is feasible and acceptable; evidence regarding how to design and implement SI programs under real-world conditions is still needed. This evaluation examined women's experiences when self-injection of subcutaneous depot medroxyprogesterone acetate (DMPA-SC) was introduced in Uganda alongside other contraceptive options in the context of informed choice. We conducted structured survey interviews with 958 randomly selected SI clients trained in three districts in 2019. SI clients demonstrated their injection technique on a model to permit an assessment of injection proficiency. A randomly selected subset of 200 were re-interviewed 10–17 months post-training to understand resupply experiences, waste disposal practices and continuation. Finally, we conducted survey interviews with a random sample of 200 clients who participated in training but declined to self-inject. Data were analyzed using Stata IC/14.2. Differences between groups were measured using chi square and t-tests. Multivariate analyses predicting injection proficiency and SI adoption employed mixed effects logistic regression. Nearly three quarters of SI clients (73%) were able to demonstrate injection proficiency without additional instruction from a provider. Years of education, having received a complete training, practicing, and taking home a job aid were associated with higher odds of proficiency. Self-reported satisfaction and continuation were high, with 93% reinjecting independently 3 months post-training. However, a substantial share of those trained opted not to self-inject. Being single, having a partner supportive of family planning use, training with a job aid, practicing, witnessing a demonstration and exposure to a full training were associated with higher odds of becoming an SI client; conversely, those trained in a group had reduced odds of becoming an SI client. The self-care program was successful for the majority of women who became self-injectors, enabling most women to demonstrate SI proficiency. Nearly all those who opted to self-inject reinjected independently, and the majority continued self-injecting for at least 1 year. Additional research should identify strategies to facilitate adoption by women who wish to self-inject but face challenges.